Radiographic comparison of weight-bearing and non-weight-bearing positions in evaluating the distal tibiofibular syndesmosis: a single-center study of 72 ankles - Javid Mohammadzadeh Azarabadi; Neveen Shalalfa; Kemal Gökkuş; Saleh Shalalfa (Journal of Orthopaedic Surgery and Research)
Abstract Introduction The distal tibiofibular syndesmosis is a key structure for the ankle joint’s stability and function, especially when the body is weight-bearing. Recent literature indicates that weight-bearing radiographs demonstrate superior diagnostic yield compared to non-weight-bearing radiographs. This study aimed to determine the diagnostic yield of the weight-bearing compared to the non-weight-bearing radiographs. Materials and Methods A total of thirty-six healthy adult individuals, with an age group ranging from 18 to 65 years, who had never experienced any trauma, were selected for this study. We performed radiographic imaging in three planes of view: anterior-posterior, lateral, and mortise, for both ankles under both weight-bearing and non-weight-bearing conditions. The tibiofibular clear space, tibiofibular overlap, medial clear space, tibiofibular distance-lateral, anteroposterior tibiofibular ratio, and Lateral Tibial (LT) width were measured. Results Tibiofibular clear space and anteroposterior tibiofibular ratio were higher in the weight-bearing position, while tibiofibular overlap, medial clear space, and lateral tibiofibular distance were higher in the non-weight-bearing position. There was a gender effect, as males had higher values for most of the parameters; however, no significant difference was seen in the anteroposterior tibiofibular ratio and tibiofibular distance lateral. The results of this study demonstrate that X-rays of the distal tibiofibular syndesmosis reveal very different outcomes when the person is bearing weight or not pulling weight. These clinically significant differences suggest that weight-bearing radiographs may enhance the identification and diagnosis of syndesmotic injuries. Further studies will be necessary to help with the refinement of the imaging protocols and to improve diagnostic accuracy based on various types of patient demographics. Conclusion WB radiographs provide a more functionally accurate assessment of syndesmotic integrity than NWB imaging. They should be incorporated into routine diagnostic protocols, especially for active individuals and those with higher BMI. These findings support the need for demographic-specific imaging strategies to improve diagnostic precision.